La mesure des arbres et des peuplements forestiers - Rondeux, Jacques (Uliège Library, 2021)
First published in 1993, "La mesure des arbres et des peuplements forestiers" was revised in 1999. The present version is both an overhaul and an important update, taking into account the evolution of techniques for collecting and using measurements taken in forests and the growing need to understand new parameters, other than woody matter alone, with a view to improving the understanding of the forest ecosystem and the management of wooded areas. The book, one of the few in French, is designed as a reference manual on dendrometry, particularly for students who are so often conditioned to consult the Internet and use "ready-to-use" software. It is also intended for teachers, researchers and forest managers. It is deliberately built on the basis of a framework approaching the main subjects treated in a progressive manner, without sacrificing certain approaches that could be considered as belonging to the past but that could prove to be very useful for a better understanding of dendrometry and for sharing it with as many people as possible. The time is long gone when this forestry science was limited to "measuring trees" with the precise aim of knowing their volume. The book can be read at two speeds, one intended for an informed public, the other focusing more on learning./"La mesure des arbres et des peuplements forestiers" was revised in 1999. The present version is both an overhaul and an important update, taking into account the evolution of techniques for collecting and using measurements taken in forests and the growing need to understand new parameters, other than woody matter alone, with a view to improving the understanding of the forest ecosystem and the management of wooded areas. The book, one of the few in French, is designed as a reference manual on dendrometry, particularly for students who are so often conditioned to consult the Internet and use "ready-to-use" software. It is also intended for teachers, researchers and forest managers. It is deliberately built on the basis of a framework approaching the main subjects treated in a progressive manner, without sacrificing certain approaches that could be considered as belonging to the past but that could prove to be very useful for a better understanding of dendrometry and for sharing it with as many people as possible. The time is long gone when this forestry science was limited to "measuring trees" with the precise aim of knowing their volume. The book can be read at two speeds, one intended for an informed public, the other focusing more on learning.